Perbedaan Penjualan Via E-Commerce Dan Direct Selling Suku Cadang Mobil Aquarius Motor - Jeki, Jeki; Iskandar, Donant Alananto (STREAMING, 2024)
Sales through e-commerce and direct selling have become two methods commonly used in the automotive industry to market and sell auto parts. However, there is still a paucity of research investigating the differences between these two methods, particularly in the context of aquarius Motor auto parts. Aquarius Motor is a micro, small and medium enterprise. This study aims to determine the differences in sales via e-commerce and direct selling of Aquarius Motor car parts. This study used a quantitative research method with a purposive sampling technique in collecting questionnaire data from customers of Aquarius motor car parts as many as 84 respondents.